2002
DOI: 10.1074/jbc.m209322200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Two Coactivator-interacting Surfaces of the Androgen Receptor and Their Relative Role in Transcriptional Control*

Abstract: The androgen receptor interacts with the p160 coactivators via two surfaces, one in the ligand binding domain and one in the amino-terminal domain. The ligand binding domain interacts with the nuclear receptor signature motifs, whereas the amino-terminal domain has a high affinity for a specific glutamine-rich region in the p160s. We here describe the implication of two conserved motifs in the latter interaction. The amino-terminal domain of the androgen receptor is a very strong activation domain constituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 53 publications
(56 reference statements)
4
53
0
Order By: Relevance
“…We found that HEYL can repress the activity of AF1 in isolation, and furthermore, GST-HEYL was able to interact with AR through the AF1 domain (although it is not yet clear whether this interaction is direct). A characteristic of AR-AF1 is the ability of this domain to interact with the coactivator SRC1, and this interaction may be more functionally relevant than well characterized interactions of coactivators with AF2 (via LXXLL interaction motifs) as described for other nuclear receptors (41). We previously showed that HEY1 interacts with the bHLH-PAS domain of SRC1 and hypothesized that HEY1 can repress AR activity by blocking SRC1e/AR interactions and/or sequestering SRC1e from functional transcriptional complexes (25).…”
Section: Discussionmentioning
confidence: 99%
“…We found that HEYL can repress the activity of AF1 in isolation, and furthermore, GST-HEYL was able to interact with AR through the AF1 domain (although it is not yet clear whether this interaction is direct). A characteristic of AR-AF1 is the ability of this domain to interact with the coactivator SRC1, and this interaction may be more functionally relevant than well characterized interactions of coactivators with AF2 (via LXXLL interaction motifs) as described for other nuclear receptors (41). We previously showed that HEY1 interacts with the bHLH-PAS domain of SRC1 and hypothesized that HEY1 can repress AR activity by blocking SRC1e/AR interactions and/or sequestering SRC1e from functional transcriptional complexes (25).…”
Section: Discussionmentioning
confidence: 99%
“…The DAF1-hinge mutants were created by exchanging HindIII/PsyI inserts. VP16-NTD and VP16-DFQNLF are pSNATCH-II constructs described earlier as hAR and hAR 1-529 DFQNLF (16,21). The DFQNLF plasmid was described before Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike other nuclear receptors, the AR AF2 is almost not active, probably because the AR AF2-coactivator interactions are weaker if compared with, for example, the estrogen receptor (16). Instead, AF1 is the major transactivation function of the AR, and the AR-NTD is the main recruiting surface for coactivators (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pGEX-2TK-RBD, -RBD-LXXAA, -RBD1, and -RBD2 bacterial expression vectors were described previously (24). pSG5-FLAG-AR-wt, -⌬NTD, -⌬Tau5, -⌬Tau1, -⌬cTau1, -⌬F, and -G21E were described previously (16,19,37). Transfer vectors baculovirusexpressing for HA-MED1-wt, -C⌬454, -C⌬690, -C⌬918, -C⌬1215, -ERK mutant (T1032A and T1457A), and full-length FLAG-AR were generated by subcloning the corresponding epitope-tagged open reading frames into plasmids pAcSG2 or pVL1392 (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%